(untitled) (Global Journal of Science Frontier Research, 2023)
Background The Musk melon Cucumis melo is an essential herbaceous plant species in Cameroon for its nutritional and ethnomedicinal values Thus roots of this plant are not edible but are used in treating many local ailments To date there has been no report on the cytotoxicity and genotoxicity of the roots of Musk melon Therefore this study was to investigate the potential cytotoxic and genotoxic effects of aqueous extracts of the roots of C melo using the Allium cepa assay Allium bulbs were treated with six concentrations 0 g ml five g ml ten g ml 20 g ml 30 g ml and 40 g ml of aqueous extract of the roots of C melo for 96 hours and distilled water was used as the control Results The results showed significant dose-dependent p 0 05 inhibition of sprouting and growth of roots as well as mitodepressive effects on cell division in A cepa root tip cells treated with aqueous extract of the roots of C melo The results also revealed a significant increase in the dose-dependent frequency of chromosome aberrations Anaphase bridges laggards disorientation sticky metaphase and binucleation in the A cepa root tip cells Conclusions This study revealed that C melo roots have a clastogenic effect on the root tip cells of A cepa The following research will test this extract on a few cancers induced in Wistar rats